2023
DOI: 10.3390/jcs7040166
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanocomposite Electrodes/Electrolytes for Microbial Fuel Cells—Cutting-Edge Technology

Abstract: Fuel cell efficiency can be improved by using progressive electrodes and electrolytes. Green nanomaterials and green technologies have been explored for the manufacturing of high-performance electrode and electrolyte materials for fuel cells. Platinum-based electrodes have been replaced with green materials and nanocomposites using green fabrication approaches to attain environmentally friendly fuel cells. In this regard, ecological and sustainable electrode- and electrolyte-based membrane electrode assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Multiple research have provided evidence that the use of graphene-based materials for the purpose of augmenting fuel cell performance may provide substantial enhancements in energy efficiency [25]. It has been shown, for example, that GO-based nanocomposites can be used as cathode materials in PEMFCs to improve their performance and durability, as shown in a study by Kausar, A. et al [26]. As a similar study by Facure, M. H. M. et al [27] demonstrated, the use of GQD-based nanocomposites as electrode materials in DMFCs improved the power density as well as the stability of the device in comparison to conventional electrode materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple research have provided evidence that the use of graphene-based materials for the purpose of augmenting fuel cell performance may provide substantial enhancements in energy efficiency [25]. It has been shown, for example, that GO-based nanocomposites can be used as cathode materials in PEMFCs to improve their performance and durability, as shown in a study by Kausar, A. et al [26]. As a similar study by Facure, M. H. M. et al [27] demonstrated, the use of GQD-based nanocomposites as electrode materials in DMFCs improved the power density as well as the stability of the device in comparison to conventional electrode materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simultaneous treatment of wastewater during the electricity generation and the removal of metals such as chromium, copper, nickel, and zinc has gained additional importance regarding the environmental benefits (Nancharaiah et al, 2015;Hidayat et al, 2022). There are several review articles available very recently which include the focusing on functional materials (Zhu Q. et al, 2022), graphene-based materials (Aiswaria et al, 2022), carbonaceous materials (Dhilllon et al, 2022), nanomaterials (Chen et al, 2022b;Kamali et al, 2022;Dey et al, 2023;Kausar et al, 2023), anodic modification materials (Ma et al, 2023), and different types of MFCs (Gupta et al, 2023). Because the sluggish oxygen reduction reaction (ORR) kinetics is one of the main obstacles, the review which draws attention to choosing the suitable cathode materials should be urgent for the practical applications of the MFC technology.…”
Section: Introductionmentioning
confidence: 99%
“…MFC is a bioelectrochemical device that can generate energy by using electrons obtained from anaerobic substrate oxidation [9][10][11]. MFC technology has received a lot of interest in recent years [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%